The DisEntangling Chronic Obstructive pulmonary Disease Exacerbations clinical trials NETwork (DECODE-NET): rationale and vision. Issue 1 (2nd July 2020) - Mathioudakis, Alexander G.; Sivapalan, Pradeesh; Papi, Alberto; Vestbo, Jørgen
Acute exacerbations are largely responsible for the poor outcomes characterising COPD, the third leading cause of death globally and associated with a significant disability and socioeconomic burden [1, 2]. Every year, 22–40% of all people suffering from COPD experience at least one moderate or severe exacerbation, while 9–16% experience more than one [3, 4]. Exacerbations are associated with an increased risk of subsequent exacerbations, cardiac events, worse quality of life and an accelerated lung function decline [5]. 15% of all severe exacerbations requiring hospitalisation lead to death within 90 days [6]. Thus, it is not surprising that patients consider exacerbations and hospitalisations due to exacerbations the most important, burdensome outcomes of COPD [7]. The DisEntangling Chronic Obstructive pulmonary Disease Exacerbations clinical trials NETwork: #DECODE_NET. Vision statement of an emerging, global network aiming to conduct collaborative clinical research on COPD exacerbation management @ERSpublications https://bit.ly/36kISgp